Distribution of the Prufer angle in p-Laplacian eigenvalue problems - Yan-Hsiou Cheng (Electronic Journal of Differential Equations, 2014)
The Prufer angle is an effective tool for studying Sturm-Liouville problems and p-Laplacian eigenvalue problems. In this article, we show that for the p-Laplacian eigenvalue problem, when x is irrational in (0,1), a sequence of modified Prufer angles (after modulo $π_p$) is equidistributed in $(0,π_p)$. As a function of x, $ψ_n$ is also asymptotic to the uniform distribution on $(0,π_p)$.